-2v+7=1+3v-6v

Simple and best practice solution for -2v+7=1+3v-6v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2v+7=1+3v-6v equation:



-2v+7=1+3v-6v
We move all terms to the left:
-2v+7-(1+3v-6v)=0
We add all the numbers together, and all the variables
-2v-(-3v+1)+7=0
We get rid of parentheses
-2v+3v-1+7=0
We add all the numbers together, and all the variables
v+6=0
We move all terms containing v to the left, all other terms to the right
v=-6

See similar equations:

| X/12=1/3-x/12 | | 90=-18v | | -8v+6(v+7)=38 | | 9(x-1)-8=5x+4(-3+x) | | 9(x-1)-8=5x+4(-3+x | | -102-2x=-7 | | 2(3b+6)=-(8-4b) | | 4k=1.5k+50 | | 4x+5x+6=10 | | F(x)=15+2x^2 | | -39+3v=5(v-5) | | 5b-4-4=7b+8 | | −2(3z+1)−10=4−2(3z+1)−10=4 | | F(-4)=12-3x | | 3x=−21​ | | (4x+1)+(5x-6)=76 | | 9x-4=2x=10 | | 8−3/2b=118−32b=11 | | (4x+1)+(5x-6)=80 | | 8-5x+10x=-2 | | 6x3-6=12 | | ​1.3x=12 | | ​1.3x=123x=12 | | –5b+21+2b=–7 | | .2(3g-5)-5=0 | | 4x-1+6=5 | | 5+6n+6n=7n-4+8n | | x+0.35x=0 | | 5|x-6|=8 | | 3x+18=11x-12 | | 3(w+3)-2=19 | | x=(3*9*(3+(9*3/(3)))); |

Equations solver categories